Cardiovascular diseases may play a negative role in the prognosis of amyotrophic lateral sclerosis. (15th April 2018) - Mandrioli, J.; Ferri, L.; Fasano, A.; Zucchi, E.; Fini, N.; Moglia, C.; Lunetta, C.; Marinou, K.; Ticozzi, N.; Drago Ferrante, G.; Scialo, C.; Sorarù, G.; et al.
Abstract : Background and purpose: Only a few studies have considered the role of comorbidities in the prognosis of amyotrophic lateral sclerosis (ALS) and have provided conflicting results. Methods: Our multicentre, retrospective study included patients diagnosed from 1 January 2009 to 31 December 2013 in 13 referral centres for ALS located in 10 Italian regions. Neurologists at these centres collected a detailed phenotypic profile and follow‐up data until death in an electronic database. Comorbidities at diagnosis were recorded by main categories and single medical diagnosis, with the aim of investigating their role in ALS prognosis. Results: A total of 2354 incident cases were collected, with a median survival time from onset to death/tracheostomy of 43 months. According to univariate analysis, together with well‐known clinical prognostic factors (age at onset, diagnostic delay, site of onset, phenotype, Revised El Escorial Criteria and body mass index at diagnosis), the presence of dementia, hypertension, heart disease, chronic obstructive pulmonary disease, haematological and psychiatric diseases was associated with worse survival. In multivariate analysis, age at onset, diagnostic delay, phenotypes, body mass index at diagnosis, Revised El Escorial Criteria, dementia, hypertension, heart diseases (atrial fibrillation and heart failure) and haematological diseases (disorders of thrombosis and haemostasis) were independent prognostic factors of survival in ALS. Conclusions: Our large, multicentre study demonstrated that, together with the known clinical factors that are known to be prognostic for ALS survival, hypertension and heart diseases (i.e. atrial fibrillation and heart failure) as well as haematological diseases are independently associated with a shorter survival. Our findings suggest some mechanisms that are possibly involved in disease progression, giving new interesting clues that may be of value for clinical practice and ALS comorbidity management.